The Herpes Simplex Virus 1 Immediate Early Protein ICP22 Is a Functional Mimic of a Cellular J Protein - Adlakha, Mitali (J Virol, 2020)
Molecular chaperones and cochaperones are the most abundant cellular effectors of protein homeostasis, assisting protein folding and preventing aggregation of misfolded proteins. We have previously shown that herpes simplex virus 1 (HSV-1) infection results in the drastic spatial reorganization of the cellular chaperone Hsc70 into nuclear domains called VICE (Virus Induced Chaperone Enriched) domains and that this recruitment is dependent on the viral immediate early protein ICP22. Here, we present several lines of evidence supporting the notion that ICP22 functions as a virally encoded cochaperone (J-protein/Hsp40) functioning together with its Hsc70 partner to recognize and manage aggregated and misfolded proteins. We show that ICP22 results in (i) nuclear sequestration of nonnative proteins, (ii) reduction of cytoplasmic aggresomes in cells expressing aggregation-prone proteins, and (iii) thermoprotection against heat inactivation of firefly luciferase, and (iv) sequence homology analysis indicated that ICP22 contains an N-terminal J domain and a C-terminal substrate binding domain, similar to type II cellular J proteins. ICP22 may thus be functionally similar to J-protein/Hsp40 cochaperones that function together with their HSP70 partners to prevent aggregation of nonnative proteins. This is not the first example of a virus hijacking a function of a cellular chaperone, since simian immunodeficiency virus T antigen was previously shown to contain a J domain; however, this the first known example of the acquisition of a functional J-like protein by a virus and suggests that HSV has taken advantage of the adaptable nature of J proteins to evolve a multifunctional cochaperone that functions with Hsc70 to promote lytic infection. IMPORTANCE Viruses have evolved a variety of strategies to succeed in a hostile environment. The herpes simplex virus 1 (HSV-1) immediate early protein ICP22 plays several roles in the virus life cycle, including downregulation of cellular gene expression, upregulation of late viral gene expression, inhibition of apoptosis, prevention of aggregation of nonnative proteins, and the recruitment of a cellular heat shock protein, Hsc70, to nuclear domains. We present evidence that ICP22 functionally resembles a cellular J-protein/HSP40 family cochaperone, interacting specifically with Hsc70. We suggest that HSV has taken advantage of the adaptable nature of J proteins to evolve a multifunctional cochaperone that functions with Hsc70 to promote lytic infection.